Economic Gaps In Indonesian Society, West Java Inequality Below Rid-wan Kamil's Leadership - Junaedi Junaedi (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
Wealth and inequality of wealth The Indonesian population is controlled by a handful of people, the richest 1% in Indonesia are far above the average national population. The economic inequality of the Indonesian population as measured using the Gini ratio reached 0.388 points on a scale of 0-1 points in March 2023, this figure increased by 0.007 points compared to the Gini ratio in September 2022 which was 0.381. Economic inequality in Indonesia is classified as low. This measurement uses the percentage of expenditure among the bottom 40% of the population, as a reference from the World Bank. The highest inequality was found in the Special Region (DI) of Yogyakarta with a Gini ratio of 0.459, greater than the national figure. The provinces with the highest level of expenditure inequality in 2022 are Gorontalo (0.423), DKI Jakarta (0.412), West Java (0.412), Papua (0.393), West Papua (0.384), Banten (0.377), West Nusa Tenggara (0.374), West Sulawesi (0.371), and Central Java (0.366). Of the 34 provinces, 16 provinces have poverty rates above the national rate, namely Papua (27.53%), West Papua (22.17%), East Nusa Tenggara (21.09%), Maluku (17.69%), and Gorontalo (15.52%). On the island of Java, the province with a poverty rate above the national rate is DI Yogyakarta in 12th place with a poverty rate of 11.7%. Central Java is ranked 15th with a poverty rate of 10.8%, while East Java is ranked 16th with a poverty rate of 10.37%. The provinces with the lowest poverty rates are DKI Jakarta at 3.47% and Bali at 3.79%. Meanwhile, during the leadership of Ridwan Kamil in West Java, the level of inequality as measured by the Gini ratio was 0.407 points in March 2018. Urban areas touched 0.418 points while rural areas reached 0.322. The sharpest increase occurred at the end of Emil's term of office, namely March 2023, amounting to 0.425 points. Of that figure, urban areas contributed quite a large number, namely 0.439 points, while villages contributed 0.321 points, inequality in West Java was higher in urban areas. The figure is consistently above 0.4 points, while rural areas are above 0.3 points